2004
DOI: 10.1007/s00421-004-1046-0
|View full text |Cite
|
Sign up to set email alerts
|

Power output of the lower limb during variable inertial loading: a comparison between methods using single and repeated contractions

Abstract: The power-inertial load relationship of the lower limb muscles was studied during a single leg thrust using the Modified Nottingham Power Rig (mNPR) and during cycling exercise in nine young male subjects. The relationship between peak power and inertial load showed a parabolic-like relationship for mNPR exertions, with a peak [937 (SD 246) W] at 0.158 kg m(2), this being significantly (P <0.05) different from the power generated at both the lowest [723 (162) W] and highest [756 (206) W] inertial loads. In con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 16 publications
1
14
1
Order By: Relevance
“…The linear appearance of the force-velocity relation of the knee-hip extension movement was consistent with other studies on half squat (Bosco et al, 1995;Rahmani et al, 2001), leg press (Macaluso and De Vito, 2003;Pearson et al, 2004), leg cycling (Driss et al, 1998(Driss et al, , 2002Vandewalle et al, 1987;Yamauchi et al, 2005), and arm cranking (Driss et al, 1998) exercises. Therefore, the maximum isometric force (F max ) and the maximum unloaded velocity (V max ) could be estimated by extrapolating the linear regressions.…”
Section: Article In Presssupporting
confidence: 85%
See 3 more Smart Citations
“…The linear appearance of the force-velocity relation of the knee-hip extension movement was consistent with other studies on half squat (Bosco et al, 1995;Rahmani et al, 2001), leg press (Macaluso and De Vito, 2003;Pearson et al, 2004), leg cycling (Driss et al, 1998(Driss et al, , 2002Vandewalle et al, 1987;Yamauchi et al, 2005), and arm cranking (Driss et al, 1998) exercises. Therefore, the maximum isometric force (F max ) and the maximum unloaded velocity (V max ) could be estimated by extrapolating the linear regressions.…”
Section: Article In Presssupporting
confidence: 85%
“…It has been reported that a maximum elbow flexion power is produced when the load is about one-third of the maximum isometric force and increased after the training with about one-third of the maximum isometric force (Kaneko et al, 1983;Toji et al, 1997). However, for knee-hip extension movements, our study and others (Macaluso and De Vito, 2003;Pearson et al, 2004) demonstrated that the maximum mechanical power was generated under $50% of the maximum isometric force. Therefore, different exercise intensities may have to be used in single-joint and multi-joint movements for optimizing the development of power.…”
Section: Article In Presscontrasting
confidence: 70%
See 2 more Smart Citations
“…Calculation of PP was performed similarly to that as detailed by Pearson et al . (). The inertial load of the system was set at 0.325 kg m 2 .…”
Section: Methodsmentioning
confidence: 97%